2020
DOI: 10.1111/cas.14335
|View full text |Cite
|
Sign up to set email alerts
|

Protease‐activated receptor‐2 accelerates intestinal tumor formation through activation of nuclear factor‐κB signaling and tumor angiogenesis in ApcMin/+ mice

Abstract: Hepatocyte growth factor activator inhibitor‐1 (HAI‐1), encoded by the SPINT1 gene, is a membrane‐bound protease inhibitor expressed on the surface of epithelial cells. Hepatocyte growth factor activator inhibitor‐1 regulates type II transmembrane serine proteases that activate protease‐activated receptor‐2 (PAR‐2). We previously reported that deletion of Spint1 in ApcMin/+ mice resulted in accelerated formation of intestinal tumors, possibly through enhanced nuclear factor‐κB signaling. In this study, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Moreover, the results of external validation based on five GEO datasets and prognostic meta-analysis all confirmed the relatively better robustness of the prognostic signature compared to previous studies (9,37). F2RL1, also known as protease-activated receptor 2 (PAR2), has been reported to be associated with the occurrence and development of lung adenocarcinoma (44) and intestinal tumors (45,46). A recent study revealed that hypomethylation of the F2RL1 promoter could upregulate its expression and promote the proliferation, migration, and invasion of LUAD cells (44).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Moreover, the results of external validation based on five GEO datasets and prognostic meta-analysis all confirmed the relatively better robustness of the prognostic signature compared to previous studies (9,37). F2RL1, also known as protease-activated receptor 2 (PAR2), has been reported to be associated with the occurrence and development of lung adenocarcinoma (44) and intestinal tumors (45,46). A recent study revealed that hypomethylation of the F2RL1 promoter could upregulate its expression and promote the proliferation, migration, and invasion of LUAD cells (44).…”
Section: Discussionsupporting
confidence: 65%
“…F2RL1 , also known as protease-activated receptor 2 ( PAR2 ), has been reported to be associated with the occurrence and development of lung adenocarcinoma ( 44 ) and intestinal tumors ( 45 , 46 ). A recent study revealed that hypomethylation of the F2RL1 promoter could upregulate its expression and promote the proliferation, migration, and invasion of LUAD cells ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The clinicopathological findings are further supported by work in vitro and in model systems: LX-2 hepatic stellate cells-expressing F2RL1 enhance tumor growth via angiogenesis in vivo using a xenograft of hepatocellular carcinoma model [ 60 ] and in an intestinal tumor model [ 61 ]. In a mouse model of mammary tumor virus-polyoma middle T (PyMT), F2RL1 (PAR2), but not F2R (PAR1), signaling accelerates angiogenesis and tumor growth [ 62 ].…”
Section: Discussionmentioning
confidence: 93%
“…Among the multiple participants, proteinase-activated receptor 2 (PAR-2) is one of the most important MCs-microglial interaction-related receptors. PAR-2, also known as GPR11 or F2RL1, belongs to the 7-transmembrane receptors that couple to guanosine-nucleotide-binding proteins family that are encoded by F2RL1 gene ( Kawaguchi et al, 2020 ). PAR-2 is widely expressed in mammals, especially in epidermal keratinocytes and immune cells, including neutrophils, dendritic cells, T cells, and macrophages ( Sutherland et al, 2019 ; Shah et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%